Transhiatal laparoscopic enucleation of lower thoracic esophageal leiomyoma - A. K. Kamalov; A. B. Ryabov; V. M. Khomyakov; N. N. Volchenko; I. V. Kolobaev; A. K. Kostrygin; D. D. Sobolev; A. B. Utkina; S. A. Aksenov; M. P. Makurina (Сибирский онкологический журнал, 2023)
The purpose of the study. Mesenchymal tumors of the esophagus comprise 2 % of all esophageal tumors. Leiomyosarcoma is the most common mesenchymal tumor in the esophagus (up to 80 %). It is located in the lower third of the esophagus. The main treatment modality of leiomyosarcoma is surgery. Due to the low frequency of occurrence, there are no unified approaches to the choice of surgical volume and access. Minimally invasive techniques have advantages over open approaches. However, final treatment approach depends on many factors: localization and location of the tumor around the circumference of the esophagus, as well as size. Endoscopic resection is feasible for small tumors with an intramural growth. In case of large leiomyomas, Lewis operation should be performed. In all other cases, tumor enucleation is the gold standard of treatment. The issue of minimally invasive surgical access is relevant. Thoracoscopic access has limitations for tumors located in the lower thoracic esophagus closer to the esophageal-gastric junction. In this regard, a laparoscopic approach with the possibility of transhiatal mobilization of the esophagus provides an adequate opportunity for tumor enucleation.Clinical case description. We hereby report our case study in which we employ the use of laparoscopic transhiatal enucleation to remove leiomyoma of the lower thoracic part of the esophagus. A 47-year-old female presented to P.A. Herzen Moscow Oncology Research Institute with complaints of pain in the epigastrium, discomfort behind the sternum when taking solid food. R0 resection was performed. During the one year follow-up period no sign of disease recurrence was observed.Conclusion. This approach, in our opinion, is fully justified, with careful selection of patients and compliance with guidelines of cancer surgery. Laparoscopic approach with transhiatal mobilization of the esophagus provides a good opportunity to perform the enucleation of mesenchymal tumors localized in the lower third of the thoracic region, at the level of the supraphrenic and abdominal segments.